Effects of ply orientation on nonlinear buckling of Aircraft composite stiffened panel - Ouadia Mouhat; Abdelmajid Bybi; Ahmed El Bouhmidi; Mohamed Rougui (Fracture and Structural Integrity)
In this paper the demand for curved stiffened panels composite from carbon fiber reinforced plastics (CFRP) has emerged; these structures are most frequently used in aerospace engineering. Nearly 50% of the primary structure of the Boeing 787 is made up of woven graphiteepoxy. This research emphasizes the buckling analysis of stiffened composite panels using the nonlinear, finite element modelling. The stiffened panel is assumed to be subjected to a uniform axial compression load of. For the nonlinear buckling analysis, a stiffened composite panel is made of carbon fibre composite (CFC) in epoxy, Kevlar in epoxy and E-glass (EG) in epoxy. Due to the fact that there are many stiffened composite panels materials, this paper therefore uses a numerical approach, to present the study and results of the nonlinear static buckling analysis of I-stiffened, on various composite panels. This research also presented theeffectof the differentply orientationsusing Abaqusfinite element analysis (FEA)